Clubes de leitura: proposta de um aplicativo para gerenciamento e compartilhamento de leituras literárias e incentivo à leitura - ALCÂNTARA, Erlane Maria de Sousa (2022)
Information and Communication Technologies (ICT) have revolutionized the production and access to information. The way of consuming information and cultural content over the internet through mobile devices has given rise to new paradigms in the practice of reading. However, despite the mass dissemination and diffusion of mobile devices and the internet, reading is not a recurring habit in the lives of most Brazilians. For this reason, initiatives that advocate and value the habit of reading, just look at reading clubs, are relevant and necessary to change the portrait of a Brazil that reads little. Thus, the purpose of this work is to promote reading clubs in Brazil through an application for managing and sharing literary reading and encouraging reading. The work was characterized as applied and technological research in terms of its purpose; exploratory and descriptive research, regarding the proposed objectives; and bibliographic research and survey regarding the technical procedures used. A prospective study was carried out on apps and/or software in order to identify national apps similar to the proposed technological solution. The prospective study carried out in the INPI Computer Programs Base and in the Play Store did not identify, until February 2022, any similar national application or software. A survey was also carried out with reading clubs in Brazil, using a semi- structured questionnaire as an instrument, in order to map, reveal profiles, raise club management characteristics to assist in the development of the web application. The modus operandi and characteristics of the book clubs were identified, confirmed and captured functionality requirements present in the app's initial proposal and for a future version. The brand of the app was created, which was preceded by a prior art search in the INPI database. The trademark registration process has already had its formal examination concluded and the publication of the registration request for opposition appears in RPI no 2696, under no 927734117. The first version of the Reading Clubs App was completed, remaining for usability and functionality testing with stakeholders: mediators or coordinators of reading clubs and club members of readers, and registered with the INPI with process No BR512022003624-0.